INTEGRASI SISTEM INFORMASI DALAM MENDUKUNG PERKEMBANGAN BISNIS PT. SANDHY PUTRA MAKMUR (SPM) CAB. SUMATERA UTARA - FACHRUR RAZI JUNED (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2014)
Information age of today requires companies to be able to follow the changes in various fields. To win the competition, companies must have the competitive advantage of one of them with strategic planning supported by information systems strategic planning. PT. Sandhy Putra Makmur (SPM) in the field of building management, noting the decline in profit margins, in 2008, Cushman & wakefield, conduct research and analysis maps GSD position in the research, noted SPM has a weakness in the field of IS / IT. To win the competition and increase company profit, SPM needs to design a strategic plan of IS / IT that aligned with business strategy. The basic concept used in preparing the integration of information systems and business strategy at the SPM is to use the methodology proposed by King danTeo, in his journal, entitled Integration Between Business Planning and Information System Planing: validating a Stage hypothesis. Research methodology which, among others, with interviews, studying documents and observations of the business activities and reviewing and analyzing the theoretical basis used in preparing the framework of the strategic plan of IS / IT. The outcome of the study was to determine factors - factors into the strengths and weaknesses of the SPM provides a framework of strategic planning of IS / IT that integrated so as to facilitate management of managing resources to produce the information needed, and can be used jointly by both SPM management centrally or at the branch office.